Covid 19 and beyond: a procedure for HVAC systems to address infectious aerosol illness transmission - Walkinshaw, Douglas Stuart; Horstman, Raymond Henry (Frontiers in Built Environment, 2023)
From pandemic level to seasonal, infections can be driven by infectious aerosol inhalation (less than 5 micron airborne particles that can stay aloft for hours) shed by ill persons, both during normal breathing or talking as well as by coughing, singing or sneezing. Inhalation dose is dependent inter alia on virion airborne concentration, occupant activity levels and exposure duration. Virion aerosol concentration is dependent upon infector shedding rate, equilibrium airborne concentration as determined by the per person ventilation rate, and the lag time to reach equilibrium as set by the spatial air change rate. To make a setting thermally comfortable, HVAC systems typically use conditioned recirculation air rather than more expensive conditioned outdoor air beyond that required by building code. But can recirculation air when filtered with non-HEPA filters remove infectious aerosols? Yes they can and a procedure is illustrated that calculates the amount recirculation air passing through a specified filter is needed to augment the code-required outdoor air supply rate so together they reduce airborne infection transmission risk to a target reproduction number for a design occupancy period germane to each setting. The reproduction target set here if implemented for HVAC systems could substantially reduce the number of respiratory infections occurring seasonally such as the common cold and help supplement mask-wearing during a pandemic. The procedure is illustrated for the following example settings: aircraft, auditorium, bar, classroom, daycare residence, gambling casino, lecture classroom, lecture hall, mall, music/theater/dance studio, office, restaurant, retail sales store, and a spectator area in a sports arena.